Elevated Serum Levels of Isoprostane and Glutathione in Waste Landfill Workers - Ari Irawan; Tri Wahju Astuti; Fitri Indah Sari; Rezki Tantular; Sastia Rakhma (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Waste landfill workers are frequently exposed to air pollutants, bioaerosols, and heavy metals, which may induce oxidative stress. Biomarkers such as isoprostanes and glutathione can be used to assess oxidative stress and antioxidant responses associated with landfill exposure. Methods: This cross-sectional study included 68 landfill workers, categorized by exposure duration into <5 years, 5-10 years, and >10 years. Isoprostane and glutathione levels were measured using an enzyme-linked immunosorbent assay (ELISA) test. A one-way analysis of variance (ANOVA) and Spearman’s correlation were used to compare biomarker levels across exposure groups and assess the relationship between biomarker levels and exposure groups. Results: Landfill workers averaged 596.01 pg/mL isoprostane. This figure is higher than the normal range of 35±6 pg/mL. The average serum glutathione level was also higher than the normal range (16.44±3.85 ng/mL). Meanwhile, the participants’ average serum glutathione level was 45.96 ng/mL. Compared to those exposed for <5 years (533.09 pg/mL), workers exposed for >10 years had higher isoprostane levels (643.94 pg/mL) (p=0.001). Thus, there was a positive correlation between exposure duration and isoprostane (r=0.331, p=0.006). Similarly, glutathione levels were higher in workers with >10 years of exposure (49.00 ng/mL) than in those with <5 years of exposure (41.20 ng/mL) (p=0.026) and showed a positive correlation (r=0.322, p=0.007). Conclusion: Long-term exposure to landfills is associated with higher serum levels of isoprostane and glutathione. It increases the risk of oxidative stress and adaptive antioxidant responses.